2016
DOI: 10.1155/2016/4394261
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Cognitive Function by Lepidium meyenii (Maca) Is Associated with Improvement of Mitochondrial Activity and Upregulation of Autophagy‐Related Proteins in Middle‐Aged Mouse Cortex

Abstract: Maca has been used as a foodstuff and a traditional medicine in the Andean region for over 2,000 years. Recently the neuroprotective effects of maca also arouse interest of researchers. Decrease in mitochondrial function and decline in autophagy signaling may participate in the process of age-related cognitive decline. This study aimed to investigate if maca could improve cognitive function of middle-aged mice and if this effect was associated with improvement of mitochondrial activity and modulation of autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In the group where cyclophosphamide with Maca at 1,000 mg/kg was administered (Figures 3d and 4d), there was marked swelling of the ducts with loss of epithelial integrity and cells; cellular/sperm debris within the lumen was however decreased. Weight loss is a common side-effect of cyclophos- CYP-treated mice; this is in contrast to the results of a number of studies that have reported that Maca administration did not have significant effects on body weight (Bilal et al, 2016;Chung, Rubio, Gonzales, Gasco, & Gonzales, 2005;Guo et al, 2016;Ruiz-Luna et al, 2005), or that it lowered body mass index (Gonzales, 2012). At 1,000 mg/kg (Figures 3f and 4f), minimal swelling of the epididymal ducts, with increase in sperm concentration within the lumen of the epididymis was observed.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter mentioning
confidence: 57%
See 1 more Smart Citation
“…In the group where cyclophosphamide with Maca at 1,000 mg/kg was administered (Figures 3d and 4d), there was marked swelling of the ducts with loss of epithelial integrity and cells; cellular/sperm debris within the lumen was however decreased. Weight loss is a common side-effect of cyclophos- CYP-treated mice; this is in contrast to the results of a number of studies that have reported that Maca administration did not have significant effects on body weight (Bilal et al, 2016;Chung, Rubio, Gonzales, Gasco, & Gonzales, 2005;Guo et al, 2016;Ruiz-Luna et al, 2005), or that it lowered body mass index (Gonzales, 2012). At 1,000 mg/kg (Figures 3f and 4f), minimal swelling of the epididymal ducts, with increase in sperm concentration within the lumen of the epididymis was observed.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter mentioning
confidence: 57%
“…Mechanisms responsible for this would include a direct effect upon energy metabolism, and more recently, there are suggestions of the antiproliferative effects of cyclophosphamide on adipocyte progenitors (Myers et al, 2017). However, administration of CYP-treated mice; this is in contrast to the results of a number of studies that have reported that Maca administration did not have significant effects on body weight (Bilal et al, 2016;Chung, Rubio, Gonzales, Gasco, & Gonzales, 2005;Guo et al, 2016;Ruiz-Luna et al, 2005), or that it lowered body mass index (Gonzales, 2012). In the present study, administration of Maca by gavage increased weight gain in mice where Maca alone was administered and mitigated weight loss following CYP administration.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter mentioning
confidence: 99%
“…is a cruciferous plant that has been used as a functional food for centuries because of its high nutritional value and health benets. [13][14][15] Maca and its extracts exert various physiological activities such as anti-oxidative, 16 anti-fatigue, 17 and anti-osteoporotic effects, 18 promote spermatogenesis, 19 treat menopausal symptoms, 20 and especially improve depression symptoms, [21][22][23] improve cognitive function, 24 and prevent memory impairment. [25][26][27] Maca lipophilic extract containing macamides has shown neuroprotective effects against middle cerebral artery occlusion in vivo and H 2 O 2 injury in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Macamides are representative lipophilic constituents of Lepidium meyenii (Maca), with various promising pharmacological properties, including neuroprotective, anti-fatigue, and fertility improving effects [ 1 , 2 , 3 , 4 , 5 ]. In previous reports, they were demonstrated to act on CB1 receptor for their neuroprotective activity against Mn-induced mitochondrial depolarization and toxicity in U-87 cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%